Passively Q-switched Erbium-doped and Ytterbium-doped fibre lasers with topological insulator bismuth selenide (Bi2Se3) as saturable absorber. (February 2017) - Haris, H.; Harun, S.W.; Muhammad, A.R.; Anyi, C.L.; Tan, S.J.; Ahmad, F.; Nor, R.M.; Zulkepely, N.R.; Arof, H.
Abstract: This paper portrays a simple Q-switched Erbium-doped fibre (EDF) and Ytterbium doped fibre (YDF) lasers by using topological insulator (TI) Bismuth Selenide (Bi2 Se3 ) as saturable absorber. The modulation depth of the fabricated Bi2 Se3 is about 39.8% while its saturating intensity is about 90.2 MW/cm 2 . By depositing the TI Bi2 Se3 SA onto fibre ferrules and incorporate it inside the proposed cavity, a stable Q-switching operation was achieved at 1 μm and 1.5 μm. The fabricated Bismuth Selenide (Bi2 Se3 ) as saturable absorber (SA) is a broadband SA where it offers a compact and low cost fabrication which is beneficial in various photonic applications. Highlights: Q-switching fibre laser using Topological Insulator (TI) Bismuth Selenide (Bi2 Se3 ). Steady and wide Q-switching pulse operation with a repetition rate of 62.5 kHz attained. Peak power of 1.15 mW was when input power is at 117.3 mW.